Job tasks and the comparative structure of income and employment: Routine task intensity and offshorability for the LIS - Matthew C. Mahutga; Michaela Curran; Anthony Roberts (Luxembourg Income Study (LIS), 2018)
Comparative sociologists have long considered occupations to be a key source of inequality. However, data constraints make comparative research on two of the more important contemporary drivers of occupational stratification - globalization and technological change - relatively scarce. This article introduces a new dataset on occupational "routine task intensity" (RTI) and "offshorability" (OFFS) for use with the Luxembourg Income Study (LIS) Database. To produce these data, we recoded 23 country-specific occupational schemes (74 LIS countryyears) to the two-digit ISCO-88 scheme. When combined with the handful of LIS countries already reporting their occupations in ISCO-88, we produce individual level RTI and OFFS scores for 38 LIS countries and 160 LIS country-years. To assess the validity of these recodes, we compare average labor-income ratios predicted by recoded ISCO-88 occupational categories to those predicted by reported ISCO-88 occupational categories within countries that transitioned from country-specific to ISCO-88 codes over time. To assess the utility of these RTI and OFFS scores and advance the literature on income polarization, we analyze their association with work hours and labor incomes in the global North and South. Both covariates correlate with work hours in ways that are consistent with previous research and additional theoretical considerations. Moreover, we show that both RTI and OFFS contribute to income polarization directly in the North, but not in the South. This article generates a public good data infrastructure that will be of use to a wide variety of social scientists, and brings new evidence to bear on the question of income polarization in rich democracies.
Keywords: 330; Inequality; Income Distribution; Income Spread; Wage Distribution; Wage spread; Labor Market Outcomes; Wages; Earnings; Pay; Labor Force Participation; Employment; Work; Hours; Measurement; Methodology; Microdata